1985
DOI: 10.1093/geronj/40.2.205
|View full text |Cite
|
Sign up to set email alerts
|

Memory for Self-Generated Stimuli in Young and Old Adults

Abstract: Young and elderly adults were required to generate or study synonyms or rhymes of stimulus words. In one experiment, multiple-trial free recall was used to assess possible developmental differences in the generation effect, a 48-hr delayed recognition task was used in the second experiment. There was a significant generation effect for young and old adults on both retention tasks. The effect, however, did not emerge for the elderly participants in free recall until the second or third trial. The implications o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
12
0

Year Published

1988
1988
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 0 publications
3
12
0
Order By: Relevance
“…To test this hypothesis, participants either read or generated words from fragments at study. Previous research has shown that generating items leads to superior recall than simply reading them (e.g., Slamecka & Graf, 1978), and older adults typically exhibit the same benefits from generating as younger adults though age differences are still apparent in the generate condition (Johnson, Schmitt, & Pietrukowicz, 1989;McFarland, Warren, & Crockard, 1985;Mitchell, Hunt, & Schmitt, 1986;Rabinowitz, 1989). Because generating words leads to greater elaboration on the target word (and presumably requires more processing resources than reading), the prediction was that DA costs would be greatest when generating and that older adults would show a smaller generation effect (relative to younger adults) under DA conditions.…”
Section: The Present Studymentioning
confidence: 96%
“…To test this hypothesis, participants either read or generated words from fragments at study. Previous research has shown that generating items leads to superior recall than simply reading them (e.g., Slamecka & Graf, 1978), and older adults typically exhibit the same benefits from generating as younger adults though age differences are still apparent in the generate condition (Johnson, Schmitt, & Pietrukowicz, 1989;McFarland, Warren, & Crockard, 1985;Mitchell, Hunt, & Schmitt, 1986;Rabinowitz, 1989). Because generating words leads to greater elaboration on the target word (and presumably requires more processing resources than reading), the prediction was that DA costs would be greatest when generating and that older adults would show a smaller generation effect (relative to younger adults) under DA conditions.…”
Section: The Present Studymentioning
confidence: 96%
“…Primary studies were excluded for a number of reasons, including the use of memory tests other than free recall, cued recall, or recognition (e.g., J. C. Brown et al, 1993;Java, 1996); bilingual subjects (e.g., O'Neill, Roy, & Tremblay, 1993); subjects from clinical samples (e.g., Pring, 1988); or pictures as stimuli (e.g., Peynircio lu, 1989). In addition, only the data from initial tests were used in studies that reported the results of multiple-trial testing (e.g., McFarland, Warren, & Crockard, 1985). Studies were excluded if they lacked the necessary statistical information (e.g., Mitchell, Hunt, & Schmitt, 1986), or if they reported results of read-only or generateonly conditions, without a comparison group in the other condition (e.g., A. S. Brown & Mitchell, 1991).…”
Section: Moderatorsmentioning
confidence: 99%
“…Given an unimpaired lexical access process and the relatively automatic nature of the generation effect, as described previously, it is predicted that older adults should show memorial benefits from generating that are just as large as those shown by younger adults. Young and older adults have been compared in generation tasks in three recent reports, with somewhat conflicting results (McFarland, Warren, & Crockard, 1985; Mitchell et al, 1986; Smith, Benham, & Leubecker, 1984). Therefore, these experiments were also designed to determine whether the generation task provides a memorial benefit for older adults.…”
mentioning
confidence: 99%